Religious Hospitals and Patient Choice - Sawicki, Nadia N. (The Hastings Center report, 2016)
Recent media reports have drawn widespread attention to the experiences of patients who are denied reproductive services at Catholic hospitals. For some patients, such as those experiencing miscarriage, denial of appropriate treatment can lead to serious health consequences. However, many patients are unaware of the limitations on services available at religiously affiliated health care institutions. As a result, patients’ ability to make informed and autonomous decisions about where to seek treatment is hindered. There are currently no federal or state laws requiring health care institutions to inform patients directly of the full scope of medical services they are unable to provide on the basis of religion or conscience. Given religious hospitals’ significant role in the provision of health care in the United States, it is essential that patients be clearly informed about institutional limitations on care. This goal would be best served by adopting a federal disclosure law similar to the Patient Self-Determination Act.